Mempertahankan Citra Perusahaan Dengan Meningkatkan Marketing Public Relations Dan Service Quality - Norbaiti Norbaiti; Rizky Nastiti (At-Tadbir : jurnal ilmiah manajemen, 2021)
This research aimed to analyze the effect of marketing public relations and service quality on corporate image of PT. Delta Abadi Sentosa in Banjarmasin. This research employed explanatory research type. The population of this study was the customers of PT. Delta Abadi Sentosa Banjarmasin. The number of samples was 100 respondents taken by using purposive sampling. The data were collected through observation, questionnaires, and documentation. The instrument test was done by using validity and reliability tests. Moreover, multiple linear regression model was employed to analyze the data. The results of the analysis showed that simultaneously marketing public relations and service quality affected corporate image. In addition, marketing public relations had a positive and significant influence on the corporate image of PT. Delta Abadi Sentosa Banjarmasin. Moreover, service quality also had a positive and significant influence on corporate image of PT. Delta Abadi Sentosa Banjarmasin.Keywords: Marketing Public Relations, Service Quality, Corporate Image